2017
DOI: 10.1002/alr.21985
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of surfactant protein A in bacterial sinusitis

Abstract: Background Chronic rhinosinusitis (CRS) is a common inflammatory disorder of the upper airway characterized by chronic inflammation and significant sinonasal remodeling. CRS has two major subgroups based on whether polyps are present or absent. In some cases, it is characterized by colonization with opportunistic pathogens such as Pseudomonas aeruginosa (PA), Staphylococcus aureus and other bacteria. The innate immune system of the sinonasal epithelium is the first line of defense against inhaled pathogens. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…Surfactant is a major component of the innate immune system; it mainly consists of phospholipids that biologically coat the gel layer, reducing the surface tension and the mucous viscosity in the respiratory system . Recent studies have suggested that surfactant protein A is expressed in the sinuses and that it plays a role in the sinus innate immune responses during bacterial infections . Furthermore, the antimicrobial potential secondary to the ability to disrupt cell membranes and eradicate bacterial biofilms is also described as a therapeutic benefit of surfactants in the setting of CRS .…”
Section: Resultsmentioning
confidence: 99%
“…Surfactant is a major component of the innate immune system; it mainly consists of phospholipids that biologically coat the gel layer, reducing the surface tension and the mucous viscosity in the respiratory system . Recent studies have suggested that surfactant protein A is expressed in the sinuses and that it plays a role in the sinus innate immune responses during bacterial infections . Furthermore, the antimicrobial potential secondary to the ability to disrupt cell membranes and eradicate bacterial biofilms is also described as a therapeutic benefit of surfactants in the setting of CRS .…”
Section: Resultsmentioning
confidence: 99%
“…The innate immune system is a common theme in several of the articles in this month's issue of the International Forum of Allergy & Rhinology ( IFAR ). The innate immune system is made up of the transmembrane proteins toll‐like receptors (TLRs) that are able to recognize consistencies found in various pathogens . These patterns are referred to as pathogen‐associated molecular patterns (PAMPs) and include highly conserved structures that are unique to the bacterial organisms.…”
mentioning
confidence: 99%
“…These patterns are referred to as pathogen‐associated molecular patterns (PAMPs) and include highly conserved structures that are unique to the bacterial organisms. Structures such as the frequency of a cytosine nucleotide followed by a guanine nucleotide, lipopolysaccharides in gram‐negative bacteria, and lipoteichoic acid in gram‐positive bacteria can all stimulate a TLR, activating the innate immune system . Once activated, antimicrobial cytokines, chemokines, proteins, and peptides are released.…”
mentioning
confidence: 99%
See 2 more Smart Citations